A multi-criteria decision-making framework for residential building renovation using pairwise comparison and TOPSIS methods. (1st August 2022) - Pinzon Amorocho, Jerson Alexis; Hartmann, Timo
Abstract: The rate at which buildings are renovated across Europe is expected to increase in the upcoming years. However, selecting renovation solutions for residential buildings is still a challenging task due to the participation of multiple stakeholders, lack of clear decision-making procedures, and diverse effects resulting from the renovation alternatives. Most of the existing approaches do not consider multiple stakeholders and focus mainly on weighting criteria and performing simulations to quantify alternatives' performance. Therefore, this paper presents a more complete Multi-criteria decision-making (MCDM) framework to support the decision-making process in renovation. To illustrate and validate the framework, it is implemented in two case studies based on a five-story building located in Spain. Each case includes five stakeholders. Two weighting settings are analysed to study the robustness and sensitivity of the proposed approach. The main contributions correspond to: 1) an MCDM enabling the participation of multiple stakeholders using the Pairwise comparison method; supporting the setting of objectives and criteria, promoting a comprehensive evaluation of the alternatives; and facilitating the integration of criteria weights and alternatives' performance through the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method; and 2) the validation of the proposed framework, especially the implementation of TOPSIS to evaluate renovation alternatives. Promoting the setting of objectives and criteria can enable discussions and encourage a broader and more complete analysis of renovation alternatives. In the two case studies, stakeholders included social aspects and assigned in total weights around 20% to this category. The Pairwise comparison and TOPSIS methods integrated the perspectives of stakeholders with different interests and the alternatives' performance to obtain a shared view of the renovation and a final ranking of the alternatives to differentiate them accordingly and make a better-informed decision. Highlights: Selection of renovation options multiple stakeholders not a single decision-maker. Objectives-criteria setting promotes a more complete evaluation of renovation options. Stakeholder's preferences integrated with alternatives' performance in renovation. TOPSIS differentiates renovation alternatives to support decision-making.